Power quality assessment of when a microgrid containing a diesel generator and/or solar PV is islanded - Allessing, Chaniel Precious (My University, 2021)
Distributed Generation (DG) plays a significant role in improving the reliability of a power supply. However, connecting DGs into the network also introduces a possibility of islanding that could create power quality issues in the network. A 400V microgrid connected to a 22 kV rural network was simulated using DIgSILENT PowerFactory software. The microgrid contained a Synchronous Generator (SG) with a diesel engine as a prime mover or Solar Photo Voltaic (SPV) or a SG in parallel with SPV. The frequency and voltage disturbances after islanding were investigated. The diesel engine was modelled with a governor (Degov) and the SG had an Automatic Voltage Regulator (AVR)(AC5A). The SPV was modelled using the WECC distributed PV plant generic model (PVD1). Three different cases concerning the types of load were analysed: static pure resistance, static series RL and composite (both a dynamic load(induction motor)and a static load). Various SG active power and SPV active power percentage contributions to the load demand during the grid-connected condition were also studied. The voltage and frequency behaviour after the islanding varied with both the SPV and the DG active power percentage contributions prior to the islanding. The voltage and frequency behaviour of the different types of DGs differed based on the cause of the islanding: sectionalisation (disconnection without a fault) or clearance of an upstream three-phase fault(disconnection with a fault). For a DG of a diesel generator and/or SPV, the purely resistive load and the series RL load showed similar trends of voltage disturbance(decrease in voltage)and frequency disturbance (decrease in frequency) during islanding. It was also observed that the voltage disturbance of the network is affected by the location of the three-phase short-circuit fault. Power quality issues are mostly observed for DG with a lower percentage active power contribution prior to the islanding and for islanding following a three-phase short-circuit fault
A dissertation submitted to the Faculty of Engineering and the Built Environment, University of Witwatersrand, Johannesburg, in fulfilment of the requirements for the degree of Master of Science in Engineering